2001
DOI: 10.1128/jcm.39.1.285-292.2001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antibodies to a Pathogenic Mycoplasma in American Alligators (Alligator mississippiensis), Broad-Nosed Caimans (Caiman latirostris), and Siamese Crocodiles (Crocodylus siamensis)

Abstract: An epidemic of pneumonia with fibrinous polyserositis and multifocal arthritis emerged in captive American alligators (Alligator mississippiensis) in Florida, United States, in 1995. Mycoplasma alligatoris sp. nov. was cultured from multiple organs, peripheral blood, synovial fluid, and cerebrospinal fluid of affected alligators. In a subsequent experimental inoculation study, the Henle-Koch-Evans postulates were fulfilled for M. alligatoris as the etiological agent of fatal mycoplasmosis of alligators. That f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…Previous studies have shown that the intensity of infection cannot always be correlated with antibody titres (Ludovisi et al 2013;Pozio et al 2002;Vu Thi et al 2010). In crocodiles, interpretation of antibody titres is also complicated, as the immune response may also be influenced by age, temperature, season, and hormone levels (Brown et al 2001;Ludovisi et al 2013). Gamble et al (1996) reported on the efficacy of enzyme immunoassays to detect light infections and indicated that the time period between infection and sero-conversion of the host was problematic in surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the intensity of infection cannot always be correlated with antibody titres (Ludovisi et al 2013;Pozio et al 2002;Vu Thi et al 2010). In crocodiles, interpretation of antibody titres is also complicated, as the immune response may also be influenced by age, temperature, season, and hormone levels (Brown et al 2001;Ludovisi et al 2013). Gamble et al (1996) reported on the efficacy of enzyme immunoassays to detect light infections and indicated that the time period between infection and sero-conversion of the host was problematic in surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…In crocodiles, the potential effects of individual hormonal status, temperature fluctuations and age on the immune response (Brown et al 2001;Ludovisi et al 2013) may explain these phenomena. However, despite the observed differences between infection intensity and time to seroconversion, the lower humoral response associated with higher infection levels may also be the result of larvae being released at different intervals, which could result in smaller but repetitive responses from the host.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an indirect ELISA was developed for detecting antibodies to WNV in chickens (Johnson et al, 2003) and multiple species of wild birds (Ebel et al, 2002;Blitvich et al, 2003). To determine WNV exposure in large numbers of samples from wild and farmed alligators, we developed an indirect ELISA using a rabbit polyclonal antibody produced against alligator immunoglobulins as the secondary antibody (Brown et al, 2001). Here we present our validation findings using plasma of captive alligators that survived an epizootic of WNV infection at an alligator farm in Florida (USA).…”
Section: Introductionmentioning
confidence: 99%
“…M. alligatoris can be cultured in high numbers from the lower respiratory tract of infected individuals, where pathologic changes include fibrinous pleuritis, pulmonary edema and congestion, and diffuse interstitial to fibronecrotic pneumonia as early as 1 wk after exposure (Brown et al, 2001b;Brown et al, 2001c;Pye et al, 2001). A genome survey revealed that M. alligatoris strain A21JP2 T notably possesses the "spreading factors" sialidase and hyaluronidase, a combination unprecedented among mycoplasmas but common among other invasive pathogens, which could degrade host extracellular matrix (ECM) glycans during nutrient scavenging to contribute to disease (Brown et al, 2004).…”
Section: Introductionmentioning
confidence: 99%